2019
DOI: 10.2147/jir.s216125
|View full text |Cite
|
Sign up to set email alerts
|

<p>Investigating the effect of <em>Crocus sativus</em> L. petal hydroalcoholic extract on inflammatory and enzymatic indices resulting from alcohol use in kidney and liver of male rats</p>

Abstract: BackgroundStudies have shown that consumption of high levels of alcohol causes many negative effects on the liver and kidneys where antioxidant ingredients can be a proper solution to reducing the resulting damages. So, the present study investigated the effect of hydroalcoholic extract of Crocus sativus L. (saffron) petal with antioxidant properties on the changes in inflammatory and enzymatic indices resulting from alcohol use in the male rats’ kidney and liver.Materials and methodsAfter preparing the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…In a 6-week double-blind, placebo-controlled and randomized trial of mild-to-moderate depression, patients that received capsules of Crocus sativus L. petals benefited from a significantly better outcome than those who received the placebo [13]; a hydroalcoholic extract of saffron petals displayed a protective effect against dysregulated ovarian steroids and inflammatory markers in a mouse model of testosterone-induced polycystic ovary syndrome [38]. Moreover, for saffron petal extracts, several studies documented the antioxidant and hepatoprotective activity in cell injury in vitro models [14,[39][40][41], and the anti-inflammatory effect both in vitro [31] and in vivo [16]. Notably, although many of these studies use experimental models involving pro-inflammatory immune responses, only two works have thus far investigated macrophages as one of the possible cell targets of Crocus sativus L. petal derivatives, showing that two purified polysaccharides, not a whole petal extract, augmented the immunogenic functions of macrophage RAW 264.7 cells [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In a 6-week double-blind, placebo-controlled and randomized trial of mild-to-moderate depression, patients that received capsules of Crocus sativus L. petals benefited from a significantly better outcome than those who received the placebo [13]; a hydroalcoholic extract of saffron petals displayed a protective effect against dysregulated ovarian steroids and inflammatory markers in a mouse model of testosterone-induced polycystic ovary syndrome [38]. Moreover, for saffron petal extracts, several studies documented the antioxidant and hepatoprotective activity in cell injury in vitro models [14,[39][40][41], and the anti-inflammatory effect both in vitro [31] and in vivo [16]. Notably, although many of these studies use experimental models involving pro-inflammatory immune responses, only two works have thus far investigated macrophages as one of the possible cell targets of Crocus sativus L. petal derivatives, showing that two purified polysaccharides, not a whole petal extract, augmented the immunogenic functions of macrophage RAW 264.7 cells [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Crocus sativus L., known as saffron, is commonly used as a spice in various regions such as Spain, Morocco, and Iran. Recently, Azizi et al [ 185 ] reported that bioactive-compound-enriched Crocus sativus L. petal (safranal, crocin, myricetin, and quercetin) could ameliorate ethanol-induced liver damage by reducing inflammatory biomarker.…”
Section: Multicomponent Food Plant Extracts Against Aldmentioning
confidence: 99%
“…Saffron polyphenolic extract protected liver from ethanol by reducing inflammation in ethanol-administered rats. [185] Parsley oil ND Parsley oil (50 mg/kg bw) was given to adult male albino rats for 4 weeks.…”
Section: Tea and Coffeementioning
confidence: 99%
“…In case of the inflammatory biomarkers assessed in the duodenum, it is found that CFWE administration led to a concentration dependent downregulation of the pro-inflammatory gene Interleukin 8 or IL8 ( Figure 1 ). An in vivo study on Wistar rats demonstrated saffron petal hydroalcoholic extract’s inhibitory effects on nuclear factor (NF-κB), C-reactive protein (CRP), and interleukin-6 (IL-6) after 8 weeks [ 24 ]. In the present study, however, the expression of NF-κβ and TNF-α genes did not significantly change at 5% and 10% CFWE.…”
Section: Discussionmentioning
confidence: 99%
“…C. sativus floral bio-residues and its isolated bioactive compounds have been investigated previously via in-vitro, in-vivo, and human studies. In general, some evidence supports its effect as an antioxidant [ 11 , 19 , 20 , 21 , 22 ], anti-inflammatory agent [ 2 , 11 , 23 , 24 , 25 ], lipid lowering potential [ 22 , 26 ], hepatoprotective [ 20 ], and antidepressant activity [ 27 , 28 , 29 ]. With this study, we aim to investigate the effect of C. sativus flower water extract (CFWE) on intestinal brush border membrane functionality, morphology, iron status, intestinal gene expression, and cecal microbiome.…”
Section: Introductionmentioning
confidence: 99%